Willingness to Pay and Its Application for the Economic Valuation of Nepalese Forest Resources - Bhattarai, Bidya Nath (Economic Journal of Nepal, 2014)
This paper attempts to calculate the visible and invisible extracted benefit from forest through the contingent valuation method (CVM) in Nepalese forest sector. The whole discussion is concentrated on the glimpse of the government expenditure and peoples’ willingness to pay for the forest resources. It is concluded that the willingness to pay of local people is explained by the level of education, age, wealth, income etc. Among them, the most dominated explanatory variable is income. Willingness to Pay (WTP) of people in most of the sampled forests has high elasticity with respect to income though other variables are equally important to determine 'why' and 'how' people are ready to pay for consumption of forest utility.The Economic Journal of Nepal, Vol. 34, No. 3, July-September 2011